A new species of Liropus (Crustacea, Amphipoda, Caprellidae) from California, USA, with an illustrated key of the genus - Guerra-García, José M.; Hendrycks, Ed A. (Zootaxa, 2003)
A new species of the genus Liropus (Crustacea, Amphipoda, Caprellidae) is described based on specimens collected from a small cave of Santa Catalina Island, California. The new species, Liropus minusculus, can be distinguished from all its congeners mainly by the presence of anterolateral projections on pereonites 2, 3, and 4 (males), pereopod 5 one-articulate (although with a second article incompletely tabicated), basis of gnathopod 2 very elongate (males), and abdomen with two pairs of one-articulate appendages (males), one of them rudimentary. Up-to-date morphological comparisons among the world Liropus species are provided, together with an illustrated key to species. This is the first record of Liropus from the north-east Pacific.